Wearing Face Masks Strongly Confuses Counterparts in Reading Emotions - Carbon, Claus-Christian (Frontiers in Psychology, 2020)
Wearing face masks is one of the essential means to prevent the transmission of certain respiratory diseases such as COVID-19. Although acceptance of such masks is increasing in the Western hemisphere, many people feel that social interaction is affected by wearing a mask. In the present experiment, we tested the impact of face masks on the readability of emotions. The participants (N=41, calculated by an a priori power test; random sample; healthy persons of different ages, 18-87 years) assessed the emotional expressions displayed by twelve different faces. Each face was randomly presented with six different expressions (angry, disgusted, fearful, happy, neutral, sad) while being fully visible or partly covered by a face mask. Lower accuracy and lower confidence in one’s own assessment of the displayed emotions indicate that emotional reading was strongly irritated by the presence of a mask. We further detected specific confusion patterns, mostly pronounced in the case of misinterpreting disgusted faces as being angry plus assessing many other emotions (e.g. happy, sad and angry) as neutral. We discuss compensatory actions that can keep social interaction effective (e.g. body language, gesture and verbal communication), even when relevant visual information is crucially reduced.